Carbon tax adoption and foreign direct investment: Evidence from Africa - Mensah, L.; Bokpin, G.A.; Yiadom, E.B.; et al. (Cogent Economics & Finance, 2024)
The study investigates the effect of carbon tax adoption on foreign direct investment in Africa. We set up the Dynamic Stochastic General Equilibrium (DSGE) model and esti mate it with the different GMM techniques. The data spans from 1995 to 2019 and covers 43 Sub-Saharan African countries. Data is sourced from the World Bank’s World Development Indicators. The findings show that the unmitigated effect of the carbon tax on FDI is repressive. However, if the revenue from the carbon tax is recycled into the economy, the carbon tax will have a significant positive effect on FDI. Hence, the findings corroborate the double dividend theory. The results further suggest that a carbon tax of around US$ 8.5 per tonne is reasonable to enhance inward FDI but a carbon Taxes either above US$ 25 per tonne or below US$ 3 per tonne will be detrimental to the African region. Also, the entrenched negative relationship between FDI and taxes is worsened if the additional carbon tax is levied among high tax regimes countries than their counterparts. This study opens the frontiers to discussions on the policy implications of carbon tax introduction on the free movement of international capital. Being among the few studies to examine the effect of the carbon tax on FDI, the study makes a significant contribution to the sparse literature in the African context. The use of a stepwise approach to estimating data based on reasonable assumptions can form the basis for future research to venture into areas where data is constrained. The policy implications are that (i) carbon tax per tonne below US$ 3 or above US$ 25 is detrimental to FDI, and (ii) the negative effect of the carbon tax on FDI can be overturned by efficiently reinvesting the carbon tax revenue in the economy.
Research Article
Keywords: Carbon tax; carbon tax revenue; carbon dioxide